The Interaction of Indium(III) with Some Lewis Bases Containing Oxygen and Nitrogen as Their Potential Sites of Donation - A. Wassef, Margureite; H. Esmail, Nagwa (Asian Journal of Chemistry, 2010)
In the present paper the authors report the synthesis and characterization of cationic In3+ complexes of some Lewis bases containing oxygen and nitrogen donor sites.